(untitled) (Bangladesh Journal of Medical Science, 2026)
Introduction Primary lymphoma of the thyroid is a rare malignancy. DLBCL is also the most common subtype followed by mucosa-associated lymphoid tissue (MALT) lymphoma. Case Report Here we present a case of a 62-year-old female presented to out-patient-department with a complaint of swelling in front of her neck for four years. The swelling was diffuse, hard in consistency, approximately 9x8 cm. On USG both the lobes were bulky heterogenous with a bulky isthmus. Total thyroidectomy was performed and sections taken showed diffuse lymphomatous infiltration of the gland by atypical lymphoid cells. On applying IHC CD20, CD5, Bcl2, Cyclin D1 were diffusely positive while CD 10 was negative and ki67 showed high proliferation index. So, the final diagnosis on the basis of clinical, radiological, histomorphological, and immunohistochemical grounds was made as Mantle Cell lymphoma of the thyroid gland. Conclusion: Only four cases of MCL affecting the thyroid have been reported till now to the best of our knowledge. Hence, this is a rare case of primary mantle cell lymphoma of thyroid. Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 993-996